Practice of the Socratic Seminar Method in Teaching Speaking at the 10th Grade of State Vocational High School 3 Purwokerto - Pristiwo, Seksie Bagus; Muflihah, Muflihah (Universitas Islam Negeri Raden Intan Lampung, 2023)
Socratic Seminar is a learning method introduced by Socrates where a series of questions are used as main tool in conversations or discussions. It is generally accepted they many students cannot speak English because they think that English is difficult and they are afraid when they speak English incorrectly. Accordingly, this thesis has been written with the aim of knowing the implementation of Socratic Seminar method in teaching speaking. The subjects were 36 students at the 10th grade majoring in Kecantikan 1, State Vocational High School Purwokerto for the 2022/2023 academic year. This study used a descriptive qualitative design which was collected through observation, interviews and documentation as data. The data were analyzed qualitatively and the analysis process included data collection, data reduction, data presentation, and conclusion or verification. The results showed that the teacher said that the Socratic method could not only be used to assess students' ability to speak but also their confidence to speak in front of the class. The final results of the research show about the teacher's efforts in managing the class using the Socratic Seminar method with 3 stages. First preparation, implementation and evaluation